Evaluating Safety Management Practices and Environmental Impact in Green Supply Chain Management: Towards Holistic Improvement (Journal of Informatics Education and Research, 2025)
This study evaluates safety management practices and environmental impact within green supply chain management using an 80-question survey-based methodology. The questionnaire explores key dimensions: operational safety protocols, employee training, incident reporting, risk assessment, environmental compliance, waste management, energy efficiency, and stakeholder engagement. Respondents include logistics managers, warehouse supervisors, and transportation coordinators from leading commercial logistics firms. Data analysis reveals strengths in standardized safety procedures and regulatory compliance, but highlights gaps in proactive risk identification and continuous environmental monitoring. Results indicate a moderate correlation between robust safety practices and improved environmental outcomes, suggesting that integrated safety-environmental strategies yield holistic benefits. The survey also uncovers areas needing improvement, such as cross-functional safety training, real-time data utilization, and transparent communication of environmental goals. Findings emphasize the importance of fostering a safety culture that aligns with sustainability objectives, advocating for regular audits, employee involvement, and investment in green technologies. This research provides actionable insights for logistics organizations aiming to enhance both operational safety and environmental stewardship, supporting the transition toward more resilient and sustainable supply chain practices. The 80-question approach ensures comprehensive coverage, enabling a nuanced understanding of current practices and informing targeted recommendations for holistic improvement in green supply chain management.